Mecanismos atencionais esperados no processo de aprendizagem de alunos surdos em matemática: uma investigação em livros didáticos do PNLD 2017 - Cruz, Alanne de Jesus (2019)
The challenge of teaching hearing-impaired students is dealt with in several fields, not being any different in the teaching of mathematics. The search for adapting and getting acquainted with specific signs of the Brazilian Sign Language (BSL), as well as methodologies and tools to help the processes of teaching and learning math becomes a routine for those who teach hearing-impaired individuals. In light of this, this present research seeks to associate the interests the didactics of math to the interests of Cognitive Neuroscience, identifying attention-based mechanisms presented in the mathematical subject called Trigonometric Ratios of the Right-angled Triangle, which are capable of helping in the learning process for hearing-impaired students, from the ostensive and non-ostensive objects present in the praxeologies of math textbooks of the 9th year of elementary school, approved by the PNLD/2017. For that, the main theoretical background of this investigation is found structured in the conceptual institutionalization of three areas of knowledge: Teaching math for hearing-impaired students (VIANA, 2014; NOGUEIRA, 2013), Anthropological Theory of the Didactic (CHEVALLARD, 2018), Cognitive Neuroscience (GAZZANIGA, 2006; LENT, 2002; COSENZA and GUERRA, 2011). To understand that scenario, an analysis of historical, epistemological and regular teaching factors has been developed in order to comprehend the object of the study, as well as the target group of the research. On the other hand, the emphasis given to the ostensive and non-ostensive objects as analysis tools in order to identify which attention-related mechanisms favorably enable the learning of math for the hearing-impaired student had as its fundamental idea the association of the assumptions presented in the Anthropological Theory of the Didactic and Cognitive Neuroscience, in an attempt to justify that the dialectical manipulation between these objects can assist hearing-impaired individuals to achieve the necessary attention for learning the subject called Trigonometric Ratios of the Right-angled Triangle. The results obtained show that it is still necessary that more research about this topic is carried out. It has also been noted that the textbooks analyzed show ostensive objects that facilitate the identification of entry points to the attention-based mechanisms. However, the use of the portuguese and mathematical languages may complicate the comprehension for the hearing-impaired student.